An Optimization Model For Electrical Vehicles Routing with time of use energy pricing And partial Recharging. Issue 9 (2018) - Ferro, G.; Paolucci, M.; Robba, M.
Abstract: The reduction of greenhouse gas emissions is a priority for European Union. National Authorities are encouraged to promote the use of electric and hybrid vehicles. In this paper, the problem of planning a freight transportation service provided by electrical vehicles (EVs) is considered, and a new decision model is proposed. An extension of the Green Vehicle Routing Problem (GVRP) is formalized, adding time variant prices for energy purchase, a detailed model for EVs consumes and different types of charging modes. The main decisions for the considered problem also refer to the velocity of EVs, the loaded cargo and the battery charge at recharging nodes, with the objective of minimizing the cost for the total travel distance and that for energy purchase, which depends on the selected recharging mode. A case study is provided and the related results are discussed.